Smart hybrid AC/DC distribution network - Neo, Joel Jiun Hao (Nanyang Technological University, 2022)
This project aims to investigate the existing power infrastructures and aid in developing a robust multiple-bus smart hybrid AC/DC distribution network for future communities by improving power efficiency to reduce cost to market participants. The scope of the project will include investigating the power infrastructures, participants, and pricing strategies of the Singapore power market, investigation of AC and DC loads in the current AC distribution network and will propose a software for load management under the Singapore power market.